A Process to Analyze Strategic Design and Management Decisions Under Uncertainty in Complex Entrepreneurial Systems. Issue 6 (November 2015) - De Lessio, Mark P.; Cardin, Michel‐Alexandre; Astaman, Angel; Djie, Valerie
ABSTRACT: This paper proposes a process to support strategic design and management of complex entrepreneurial systems under uncertainty. The process is designed to help designers and decisions‐makers readily identify valuable opportunities for flexibility as a way to deal pro‐actively with uncertainty and improve strategically the lifecycle performance of the system as it is designed, deployed, and managed in operations. The process relies on the novel concept of a layered design structure matrix (DSM), which provides gradually a systems‐level representation of the enterprise system starting at an early stage, and gaining more details as more information becomes available about the system and its environment. The resulting layered DSM is used to identify performance‐enhancing flexibility strategies in the design and management of the system. The flexibility, providing the "right, but not the obligation, to change the system in the face of uncertainty" provides contingencies to minimize exposure to downside risks, and to enable the system to capture upside opportunities—thereby improving expected lifecycle performance. The process is applied as a demonstration to the analysis of a startup system in the sector of mobility on‐demand transportation. Strategic‐level opportunities for flexibility are identified systematically, and real options analysis is used to demonstrate quantitatively lifecycle performance improvement as compared to baseline design concepts.